2015
DOI: 10.2334/josnusd.57.45
|View full text |Cite
|
Sign up to set email alerts
|

CD105 expression in oral capillary hemangiomas and cavernous hemangiomas

Abstract: Capillary hemangioma (capillary lobular hemangioma) and cavernous hemangioma (venous malformation) are relatively common oral tumors/ malformations and are characterized by increased numbers of normal and abnormal blood vessels. However, the causes of these lesions are not well understood. CD105 (endoglin) is predominantly expressed in proliferating blood endothelial cells (ECs). We analyzed expressions of CD105, CD34, von Willebrand factor, Ki-67, cyclooxygenase-2 (COX-2), and vascular endothelial growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Capillary hemangioma is a common lesion, but it rarely occurs in the oral cavity. According to Matsumoto et al [ 7 ], 45.2% of capillary hemangiomas occur on buccal mucosa, 35.5% on the tongue, and only a small percentage occur in the lip, gingiva and palate. Capillary hemangiomas are firm in consistency and have a limited history of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Capillary hemangioma is a common lesion, but it rarely occurs in the oral cavity. According to Matsumoto et al [ 7 ], 45.2% of capillary hemangiomas occur on buccal mucosa, 35.5% on the tongue, and only a small percentage occur in the lip, gingiva and palate. Capillary hemangiomas are firm in consistency and have a limited history of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, diverse biological positive and negative regulators of angiogenesis have been identified for every HEM biological evolutional phase (e.g. CD31, the von Willebrand factor, the basic fibroblast growth factor or BFGF, the proliferating cell nuclear antigen, and the vascular endothelial growth factor or VEGF); it is believed that the imbalance of these regulators influences the lesion's pattern of growth (23,25,40). Oral HEMs may be associated with other craniofacial conditions, such as anterior open bite, salivary leakage, or diverse facial unacceptable deformations, as well as chewing and speaking disabilities (24).…”
Section: Discussionmentioning
confidence: 99%
“…Currently available treatment modalities. A total of nine experimental and observational/longitudinal studies were detected in this scoping review dealing with the treatment (surgical or pharmacological) and follow-up of oral and maxillofacial hemangiomas in pediatric patients (14,15,22,23,25,(40)(41)(42)(43). Although it has been reported that around 50% of HEMs regress spontaneously with no permanent damages -thus no treatment is required-, it is plenty justified a close observation of all the lesions (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Recently other treatment modalities are also developed which includes steroid therapy, electrosurgery, Nd: YAG laser, CO 2 laser, diode laser, cryosurgery and use of sclerosing agents. 12 Surgical management shouldbe executed with caution taking into consideration the possibility of bleeding intraoperatively and post-operatively.…”
Section: Discussionmentioning
confidence: 99%